THE MORPHOLOGICAL ANALYSIS BETWEEN BACK FORMATION AND CLIPPING ON TREASURE ISLAND NOVEL - Fitriana, Sisca; Lisdawati, Ida (PROJECT (Professional Journal of English Education), 2020)
This study aims to analyze the use of clipping and back formation in a novel titled Treasure Island Novel by Robert Louis Stevenson. The subject of this research is to focus on the introduction of the characters involved in this novel. The novel tells from a first-person perspective that Robert Louis Stevenson is Jim, who takes many important decisions. Other characters in this story are Squire Trelawney, Doctor Livesey, an old captain named Billy Bones, Long John Silver who has a cruel character and Black Dog captain, a blind pew and his gang. This research was conducted using descriptive quantitative methods and to process data using the frequency formula from the Guttman theory frequency. The findings of the analysis showed that the clipping frequency was 79,63% and the back formation frequency was 20,37%. The results show that in the Treasure Island Novel clipping the most dominant appeared. In the novel there are 54 sentences included in clipping and back formation, 43 sentences included in clipping and 11 sentences included in back formation. Robert Louis Stevenson in writing the Treasure Island Novel is only small part of the word that uses the process of cutting or reducing words called the process of clipping and back formation. The word that appears most in clipping is Bill (Billy Bone) and in back formation is mate (soulmate). Keywords:  Back Formation, Clipping, Morphosyntax, Word Formation